2019
DOI: 10.1111/dom.13805
|View full text |Cite
|
Sign up to set email alerts
|

Do GLP‐1RAs and SGLT‐2is reduce cardiovascular events in black patients with type 2 diabetes? A systematic review and meta‐analysis

Abstract: Aims While recent cardiovascular safety trials (CVST) concerning newer diabetes medications included mostly white participants, results are being generalized to all races in recent guidelines. This raises a controversial question regarding the appropriateness of applying CVST data to black patients with type 2 diabetes. Materials and methods We searched for randomized trials comparing diabetes medications to placebo in type 2 diabetes and investigated three‐ or four‐point major adverse cardiovascular events (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 56 publications
(206 reference statements)
1
25
0
Order By: Relevance
“…We used two previously performed and published literature searches to explore and include trials. 13,14 In addition, we searched review articles that examined completed and ongoing cardiovascular outcome trials. 15 Two Relative risks (RRs) with 95% confidence intervals (CIs) were used to summarize dichotomous data.…”
Section: Methodsmentioning
confidence: 99%
“…We used two previously performed and published literature searches to explore and include trials. 13,14 In addition, we searched review articles that examined completed and ongoing cardiovascular outcome trials. 15 Two Relative risks (RRs) with 95% confidence intervals (CIs) were used to summarize dichotomous data.…”
Section: Methodsmentioning
confidence: 99%
“…While stratification of participants according to race or ethnic groups have not identified significant differences in the cardiovascular efficacy of GLP-1RAs, [6][7][8][9] given the under-representation of these populations in CVOTs, it is currently unclear whether GLP-1RAs reduce cardiovascular risk in specific race/ethnic groups (eg, black patients). 62 Moreover, it is unknown whether this under-representation in RCTs affects routine clinical practice and GLP-1RAs prescription. In this context, RWS have shown how subjects belonging to minorities have lower probability to achieve appropriate glucose control and control of other cardiovascular risk factors.…”
Section: Effectiveness In Special Populationsmentioning
confidence: 99%
“…In fact, most of the randomized clinical trials evaluating cardiometabolic risk factor control and long-term cardiovascular and mortality risk among patients with type 2 diabetes are primarily based on white patients, with marginal representation of black populations. 17 The meta-analysis of cardiovascular outcome trials evaluating GLP-1RAs and SGLT2 inhibitors by Hoppe et al 17 and Mishriky et al 18 reported that less than 5% of the trial populations were black, and only two of these trials collected race data consistent with US Food and Drug Administration (FDA) guidelines.…”
Section: Introductionmentioning
confidence: 99%